Use of data magnetic susceptibility measurements in the thermometer deep processes - V.S. Portnov; S.A. Vyzhva; N.V. Reva; V.M. Jurov (Қарағанды университетінің хабаршысы. Физика сериясы)
We obtain the connection between the magnetic susceptibility, the Gibbs energy of minerals and iron content of the mineral. The theoretical equation of communication is in good agreement with the experimental data. A relation between the temperature of formation of the mineral and its magnetic susceptibility. Knowing the temperature of formation of minerals makes it possible not only to determine the genesis of the deposit, but also to predict the shape of ore bodies. These equations connection between the temperature of formation of minerals and measured values in a particular method of geophysical studies contain a constant that must be determined empirically, using correlation analysis. If one examines the same geological object, the temperature of its formation is the same, then it is possible to define a constant through another one. Methods for assessing the geological formation temperature of the object proposed in this paper can be implemented by means of terrestrial or space without extracting the mineral from different depths of the Earth's crust.